2021
DOI: 10.4103/npmj.npmj_636_21
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern and Prevalence of Haematological Cancers among Adults in Abakaliki, South-Eastern Nigeria

Abstract: Background: Haematological cancers are clonal diseases of the blood and blood-forming organs, with the distribution pattern not known in our locality. This study aimed to describe the distribution pattern and prevalence of haematological cancers among adults in Abakaliki, Nigeria. Materials and Methods: This was an 8-year retrospective study in which the hospital records/case notes of adult patients diagnosed and managed for haematological cancers from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In a previous study [4], the prevalence of CML was reported as 19.57%. A similar study on the pattern and prevalence of haematological cancers in South-Eastern Nigeria also reported a prevalence of 12.6% [5]. The chronic myeloid leukaemia is said to affect any age group but is rare in children [2,3].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a previous study [4], the prevalence of CML was reported as 19.57%. A similar study on the pattern and prevalence of haematological cancers in South-Eastern Nigeria also reported a prevalence of 12.6% [5]. The chronic myeloid leukaemia is said to affect any age group but is rare in children [2,3].…”
Section: Introductionmentioning
confidence: 85%
“…The median ages vary from one location to another. In the western world, it is 53 years while in African countries, it is 38years [5,6,7]. Chronic myeloid leukaemia is a bi-or triphasic disease condition.…”
Section: Introductionmentioning
confidence: 99%
“…suggest that haematological malignancies constitute significant cancer mortality and morbidity and impacting on the health and economy of many developing countries of Africa. Amongst these, MM is remarkable with a projected mortality of 91% by 2030 [7][8][9]. In spite of these indicting reports in Africa, cancer has been given low priority in the research field and health care services and only few countries have incorporated PV in the care of MM patients [10].…”
Section: Studiesmentioning
confidence: 99%